2004
DOI: 10.3171/jns.2004.101.4.0659
|View full text |Cite
|
Sign up to set email alerts
|

Induction of the DNA repair gene O6-methylguanine—DNA methyltransferase by dexamethasone in glioblastomas

Abstract: These results indicate that dexamethasone-mediated upregulation of MGMT limits the efficiency of alkylating agents in the treatment of malignant gliomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 16 publications
0
26
0
Order By: Relevance
“…In addition, MGMT expression can be regulated by TFs acting as transcriptional activators or repressors [12,36]. Although most studies addressing MGMT expression have so far focused on epigenetic mechanisms, TFs such as AP-1 [40], Sp1 [41], NF-κB [42], HIF-1α [36,43], GRE [44] and the CBP-p300 transcriptional coactivator complex [45], have also been reported to be able to up-regulate MGMT expression by enhancing the MGMT promoter activity [12,36]. On the other hand, p53 [46] and IFN-β [47] have been reported to be able to down-regulate MGMT expression.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, MGMT expression can be regulated by TFs acting as transcriptional activators or repressors [12,36]. Although most studies addressing MGMT expression have so far focused on epigenetic mechanisms, TFs such as AP-1 [40], Sp1 [41], NF-κB [42], HIF-1α [36,43], GRE [44] and the CBP-p300 transcriptional coactivator complex [45], have also been reported to be able to up-regulate MGMT expression by enhancing the MGMT promoter activity [12,36]. On the other hand, p53 [46] and IFN-β [47] have been reported to be able to down-regulate MGMT expression.…”
Section: Discussionmentioning
confidence: 99%
“…We first tested the effects of TMZ on U87-MG, U251, A172, and BT325 glioma cell lines, and found that U251, A172, and BT325 cell lines was not sensitive to TMZ. Methylation of MGMT promoter has been indicated as a common marker for predicting chemotherapy and prognosis of TMZ on glioma patient [19-21]. Consistently, U251, A172, and BT325 have unmethylated MGMT promoter, which rend them to TMZ resistance.…”
Section: Discussionmentioning
confidence: 99%
“…18) A recent experimental study has demonstrated that the induction of MGMT by dexamethasone was associated with increased resistance to ACNU in glioma cells. 22) Conversely, IFN-b down-regulates the expression of MGMT, enhancing chemotoxicity against glioma cells. 15) Therefore, the real responsiveness to adjuvant chemotherapy might be masked by these therapeutic agents.…”
Section: Discussionmentioning
confidence: 99%